DAMPAK MODEL PENDIDIKAN KELUARGA TERHADAP KONDISI PSIKOLOGIS DAN KEMANDIRIAN ANAK - Achmat Mubarok (Universitas Yudharta Pasuruan, 2020)
Parents have a very important role in the continuity of a child's life in a family. The behaviors, attitudes, and ordinances of life made by parents are the elements of education that will indirectly enter into the child's behavior. Therefore, parents should always give examples and a good example to the child in behaving. The study and discussion in this study on the impact of the family education model on the psychological and self-reliance conditions of the child and the constraints faced by parents in the implementation of family education. The family education Model is very influential in the development and growth of children, especially in the absence. The Model of Family education implementation is done by adjusting to the situation and condition of children and based on the context of the needs and abilities of the child through the provision of a set of rules that are accompanied by the provision of good motivation, the giving of the good dowager or manners, and the depth of the religious sciences owned by the parents will give a good impact on the psychological and independence , just as a child will be more controlled in prayer, diligent manners in carrying out daily and responsible tasks. The obstacles faced by parents in the implementation of family education require high process and patience, transparency, have scholarly discipline to accompany and guide the child, especially for the busy parents in the work.